Association of temperature humidity index during summer with haematological parameters in native and crossbred goats of Kerala* - Debia Yamin (Director of Academics and Research, Kerala Veterinary and Animal Sciences University, 2021)
The study was conducted to investigate the association of temperature humidity index (THI) during summer with haematological responses in Malabari, crossbred and Attappady goats of Kerala. The research work was conducted at University Goat and Sheep Farm, KVASU, Mannuthy, Thrissur district in Kerala from March to May, 2020. In-house temperature and in-house relative humidity were measured daily at 7.00 AM, 10.00 AM, 2.00 PM and 5.00 PM. Haematological parameters such as total erythrocyte count (TEC), total leucocyte count (TLC), haemoglobin concentration (Hb), volume of packed red cells (VPRC), mean corpuscular volume (MCV) and mean corpuscular haemoglobin concentration (MCHC) were analysed during 2nd, 32nd day and 60th day of the study. There was no significant change in TEC, VPRC levels in between the breeds and within the observed days. However, TLC were significantly increased for Malabari goats and MCHC were significantly increased in all the breeds at 32nd day of study period. The Hb concentration were significantly increased in crossbred and Attappady black at 32nd day of study period. There was a significant decrease in MCV values in 2nd and 32nd day for all the breeds. The study demonstrated certain altered hematological features in all the breeds under study indicating the adaptive ability of these animals during heat stress.